PEMBELAJARAN PASSING BAWAH BOLA VOLI MINI MENGGUNAKAN PERMAINAN BOLA GANTUNG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study was to determine the improvement of learning outcomes passing under a mini volleyball game using a ball hanging on Elementary School fourth grade students Srengseng 03 districts pagerbarang tegal district . This study conducted in four stages , including planning , action , observation , and reflection using the classroom action research . Each meeting shows the stages of the process of learning the material physical education volleyball . The subjects were fourth grade students of the District 03 Elementary School Srengseng Pagerbarang Tegal in 2013 numbered 20 students . The results based on the analysis of the percentage of cycle 1 and cycle percentage 55 % 85% 2 30% increase in the percentage of successful assessment of indicators of success that is expected is 85 % . Conclusion of this study indicate that the hanging ball games can improve learning passing under mini volleyball in grade IV elementary School District of Pagerbarang Srengseng 03 Tegal regency . Teachers Penjasorkes suggestions in carrying out the task of teaching should always carry out action research as a factor if there are problems inhibiting the learning process .